ANALISIS KONFLIK AGRARIA DI KAWASAN KONSERVASI STUDI KASUS TAMAN NASIONAL GUNUNG GEDE PANGRANGO - HIDAYAT, SARIF ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The seed of Its Batu Karut claim conflict in TNGGP, in fact have sprouted since the year 2006. The year 2006 PMP try to claim Its Batu Karut through the application of permission the hewing of pine to Dinas Pertanian dan Kehutanan Kabupaten Bogor. The Problem of this Batu Karut claim what then happened TNGGP reaction because considering Batu Karut is part of TNGGP management that handed over Perhutani to TNGGP since the year 2003 through SK Menteri Kehutanan No. 174 Kpts-II 2003 . Many effort to be done by a both parties in the Bau Karut claim, start from doing administrative letter to related parties up to doing the effort of yustisif through the court to get decision still about the ownership of Batu Karut. From the problem of this claim Batu Karut sole come up surface and become one of affairses conflicts are that happened in TNGGP especially and conservations area in Indonesia in general . By using this study qualitative method try to illustrate the source of conflict, dynamics kontestasi and the approach of the conflicts solutions orient curative and anticipative. This study illustrated with using the theory of biography Conflict and The Mapping of Conflicts with a concept path of thought to see role and the interest of the partieses in a conflict Batu Karut. Conclusion that gotten from the result of research is that Its Batu Karut claim by PMP, besides background overshadow by existence of SK Mendagri No. 222/DJA/1984, about the Redistribution and Herisitribusi, also because the economic value Batu Karut of the soil, land, ground, rubber and pinewood up to agrotourism value that will be developed in the area. Through SK Mendagrai No. 222 DJA 1984 this is publics were involved in the process of application of improvement of right become a public certificate of title. Based on at the condition, formulated approach solution, that is through the approach of negotiation that is is way effort to finalize conflict between both parties what have different interest with the way doing meeting between the side with conflict so that conflict can be finalized with the agreement of interest of the side both parties with conflict (TNGGP and PMP). The approach of communications that is coordination and intensive to open mutually understanding between TNGGP with BPN and Pemerintah Daerah. The Approach of Enableness of Public that is approach with a target increase ability and the independence of surounding publics of Batu Karut especially public what indigent from economic side, so that expected is able to shifting patterned thinking and its ability publics from the dependency to forest through this approach expected Batu Karut conflict was finalized based on the interest of the side with conflict, and existence of permanent support to the management of Batu Karut area either by a related institution and also surounding public of Batu Karut.